Asymmetric synthesis of syn- and anti-alpha-deuterio-beta(3)-phenylalanine derivatives - Davies, S; Foster, E; McIntosh, C; Roberts, P; Rosser, T; Smith, A; Thomson, J (2011)
The conjugate addition of lithium (S)-N-benzyl-N-(α-methylbenzyl) amide to a range of aryl substituted tert-butyl cinnamate esters followed by reaction of the resultant lithium β-amino enolates with D2O provides access to anti configured α-deuterio-β-aminocinnamate esters in high dr. The corresponding syn configured diastereoisomers were also obtained with high diastereoselectivity via the conjugate addition of lithium (S)-N-benzyl-N-(α-methylbenzyl)amide to a range of tert-butyl α-deuteriocinnamate esters followed by reaction of the resultant lithium β-amino enolates with 2-pyridone. After deprotection both the syn- and anti-diastereoisomers of the corresponding α-deuterio-β3- amino acids can be isolated in high dr. © 2011 Elsevier Ltd. All rights reserved.